Meningkatkan Minat Anak Desa Dukuh Ngerogung Ngebel Ponorogo dalam Mengikuti Madrasah Diniyah di Tengah Padatnya Sekolah dan Godaan Gadget - Amanda Elvira Maharani; Risa Alfiyah Ulfa (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The Islamic Boarding School (Madrasah Diniyah) plays a crucial role in instilling religious education, but children in Dukuh Ngrogung Village lack interest due to the busy schedule of formal schooling and the influence of gadgets. This activity aims to increase children's interest in attending the Islamic Boarding School (Madrasah Diniyah), raise awareness of the importance of religious education, and encourage parental and community involvement. The method used is ABCD (Asset-Based Community Development) with the stages of discovery, dream, design, and define & destiny. Local assets such as Madin teachers, religious leaders, prayer rooms, and community support are utilized in creative learning activities. Results show an increase in child attendance of around 30–35%, higher learning motivation, more controlled gadget use, and stronger parental and community involvement. The activity's objectives have been achieved, and the Islamic Boarding School (Madrasah Diniyah) has the potential to be sustainable.